Synthesis of omega-3 ethyl esters from chia oil catalyzed by polyethylene glycol-modified lipases with improved stability. (15th January 2019) - Castejón, Natalia; Moreno-Pérez, Sonia; Abreu Silveira, Erick; Fernández Lorente, Gloria; Guisán, José M.; Señoráns, Francisco J.
Highlights: Enzymatic synthesis of omega-3 FAEE from chia oil has been achieved. Lipase from Thermomyces lanuginosus (TLL) was immobilized and coated by a layer of PEG. Commercial lipases were compared in the transesterification of seed oil. Lipase comparison for FAEE production showed higher stability for modified lipases. Highly concentrated α-linolenic esters were produced under mild conditions. Abstract: Enzymatic synthesis of fatty acid ethyl esters (FAEE) from chia ( Salvia hispanica L.) oil has been performed with different modified derivatives and compared with commercial immobilized lipases to produce omega-3 rich FAEE. Therefore, the main objective was to synthesize omega-3 esters from chia oil catalysed by polyethylene glycol-modified lipases using a biocatalyst with higher stability than commercial derivatives. Lipase from Thermomyces lanuginosus (TLL) was immobilized by hydrophobic adsorption on Sepabeads C-18 followed by a physicochemical coating of lipase surface with a dense layer of PEG. Ethanolysis reactions were carried out using pressurized liquid extracted chia seed oil and with different lipase derivatives to compare the omega-3 FAEE yield and ratio of reaction products, which were analysed by HPLC-ELSD. Furthermore, reutilization of lipase derivatives was studied to evaluate the stability after several reaction cycles to minimize decreasing of catalytic activity and develop a feasible enzymatic process for food industrial applications.